The Effect of Workload and Worklife Balance on Employee Performance - Muhammad Rafly Revanza; Maria Ulpah; Dharliana Hardjowikarto; Muhamad Alwi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to determine the extent to which workload and work-life balance influence employee performance at PDAM Tirta Kamuning. This research adopts a quantitative approach with a correlational design aimed at explaining the relationships between variables and predicting outcomes. The sample consisted of 57 respondents, with data collected through questionnaires. The results of multiple regression analysis indicate a significant influence of Workload (X1) and Work-Life Balance (X2) on Employee Performance (Y), accounting for 21.6% of the variance. The overall conclusion and implications of the study highlight the importance of organizational commitment in addressing work-family conflict and turnover intention. The findings also show that organizational commitment serves as a mediator in the relationship between turnover intention and work-family conflict, where the majority of employees are affected by these factors, although a small portion are influenced by other factors beyond the scope of this study. Furthermore, workload was found to have a significant positive effect on employee performance, indicating that employees perceive their workload as manageable, aligned with their capabilities, and supported by sufficient time to complete tasks. Likewise, work-life balance also significantly and positively affects performance, suggesting that maintaining balance between work and personal life enhances employee productivity and effectiveness.